Implementasi Lean Six Sigma Dalam Penentuan Prioritas Perbaikan Kualitas Pelayanan Padarumah Sakit Di Kabupaten Lumajang - Ato’illah, Mohammad (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2018)
ABSTRACT. The study aims to determine the priority of quality improvement of hospital service based on perception, expectations and importance of customers by using lean six sigma approach. The results of the study are expected to contribute to hospital management in providing the best service for the community. This research determines the priority of service quality improvement of hospital based on service quality dimension consisting of (1) tangible, (2) reliability, (3) reponsiveness, (4) assurance and (5) emphaty. This study is a qualitative descriptive research intended to analyze the responses of respondents on the quality of hospital services based on perception, expectations and importance will be used to determine the priority of improving the quality of hospital services. Research respondents were 240 service users in four hospitals in Lumajang district. Data analysis technique using lean six sigma approach by first testing the research instrument with validity and reliability test. The results of the study there are differences in the order of priority of service quality improvement at four hospitals. Priority improvement in dr Haryoto hospital is the ability and dexterity in dealing with patient complaints, at the Bhayangkara hospital is the timeliness of open counter service, at Wijaya Kusuma hospital is completeness of examination equipment, and Islam hospital is the ability of the officer to explain thhe results of the examination.